GABPB1-AS1 Promotes the Development of Osteosarcoma by Targeting SP1 and Activating the Wnt/β-Catenin Pathway. (18th March 2022) - Chen, Jingyang; Bian, Meiru; Pan, Lingxiao; Liu, Chengdong; Yang, Hanshi
Abstract : In this study, the role of GABPB1-AS1 in osteosarcoma (OS) was analyzed. The expression of GABPB1-AS1 in different OS cell lines U2OS, HOS, MG63, and hFOB1.19 was detected. SiRNA GABPB1-AS1 was transfected with U2OS and HOS cell lines. The effects of GABPB1-AS1 silencing on proliferation, clonal formation, and migration of U2OS and HOS were detected by CCK-8 method, plate cloning method, and Transwell chamber. Western blot analysis was used to detect the protein levels of SP1, Wnt, β -catenin, c-Myc, and SOX2 in osteosarcoma cells. The binding relationship between GABPB1-AS1 and miR-199a-3p in OS cells was detected by a dual-luciferase reporter gene assay. Results showed that GABPB1-AS1 was higher in OS cells than that in hFOB1.19. Silencing GABPB1-AS1 inhibited the proliferation, clonal formation, migration, and epithelial-mesenchymal transformation of U2OS and HOS. There was a binding relationship between GABPB1-AS1 and miR-199a-3p in OS cells. GABPB1-AS1 mediated osteosarcoma cells via the SP1/Wnt/ β -catenin signaling pathway. This study suggested that GABPB1-AS1 plays a carcinogenic role in OS through the SP1/Wnt/ β -catenin signaling pathway through competitive binding and inhibition of miR-199a-3p.